Pengaruh Budaya Organisasi Dan Komunikasi Terhadap Kinerja Pegawai Pada Badan Pengembangan Sumber Daya Manusia Provinsi Jawa Timur - Bayu Satrio Nugroho; Rudy Handoko; Endang Indartuti (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
BPSDM East Java Province plays an important role in ensuring the existence of quality State Civil Apparatus in carrying out public services. This causes the East Java BPSDM to maximize employee performance by focusing on factors influencing Employee Performance. The purpose of the study is to analyze the impact of Organizational Culture and Communication on Employee Performance at the East Java BPSDM. The study design is quantitative with SPSS regression analysis. The study population is 218 East Java BPSDM employees. Determination of the sample through the Slovin formula so that the study sample is 141 samples. Data collection through questionnaires. The results of the study prove that Organizational Culture and Communication have a significant impact on Employee Performance partially and simultaneously.